2022
DOI: 10.1038/s41389-022-00409-3
|View full text |Cite
|
Sign up to set email alerts
|

MYCN induces cell-specific tumorigenic growth in RB1-proficient human retinal organoid and chicken retina models of retinoblastoma

Abstract: Retinoblastoma is a rare, intraocular paediatric cancer that originates in the neural retina and is most frequently caused by bi-allelic loss of RB1 gene function. Other oncogenic mutations, such as amplification and increased expression of the MYCN gene, have been found even with proficient RB1 function. In this study, we investigated whether MYCN over-expression can drive carcinogenesis independently of RB1 loss-of-function mutations. The aim was to elucidate the events that result in carcinogenesis and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 69 publications
(90 reference statements)
0
17
0
Order By: Relevance
“…This controversy has been pointed out recently by Gallie's research group as they also encountered RB patients bearing not Rb1 mutations, in which they detected high copy numbers of the MYCN gene, which is a member of MYC transcription factors (Rushlow et al, 2013). More recent research was conducted and revealed more about the mechanism and interactions between the over‐expression of MYCN and retinoblastoma (Blixt et al, 2022; Zugbi et al, 2020). Despite a low population of patients with this new subtype of retinoblastoma, MYCN amplification has been shown to cope with much lower sensitivity with standard chemotherapy of RB, hence, highly dangerous as no specific clinical guidelines to aid or salvage patient's vision (Zugbi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This controversy has been pointed out recently by Gallie's research group as they also encountered RB patients bearing not Rb1 mutations, in which they detected high copy numbers of the MYCN gene, which is a member of MYC transcription factors (Rushlow et al, 2013). More recent research was conducted and revealed more about the mechanism and interactions between the over‐expression of MYCN and retinoblastoma (Blixt et al, 2022; Zugbi et al, 2020). Despite a low population of patients with this new subtype of retinoblastoma, MYCN amplification has been shown to cope with much lower sensitivity with standard chemotherapy of RB, hence, highly dangerous as no specific clinical guidelines to aid or salvage patient's vision (Zugbi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 2 (Continued) and interactions between the over-expression of MYCN and retinoblastoma (Blixt et al, 2022;Zugbi et al, 2020). Despite a low population of patients with this new subtype of retinoblastoma, MYCN amplification has been shown to cope with much lower sensitivity with standard chemotherapy of RB, hence, highly dangerous as no specific clinical guidelines to aid or salvage patient's vision (Zugbi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the cargo limitation of AAV or other similar viral vectors, many efforts have been paid to test the applicability of non-viral retinal gene delivery, including ion electroosmosis, 11 particle bombardment, 12 electroporation (EP), 13 magnetic transfection, 14 photoporation 15 and acoustic perforation. 16 In all non-viral delivery methods, EP has emerged as one of the most likely alternatives to AAV [17][18][19][20][21] because of its high transfection efficiency 22,23 and nontoxicity. 24 Electroporation, in which high-intensity electric fields are applied to destabilize cell membranes to facilitate transmembrane particle transport, 25 has been demonstrated to be capable of delivering DNA plasmids into the retina.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the cargo limitation of AAV or other similar viral vectors, many efforts have been paid to test the applicability of non-viral retinal gene delivery, including ion electroosmosis, 11 particle bombardment, 12 electroporation (EP), 13 magnetic transfection, 14 photoporation 15 and acoustic perforation. 16 In all non-viral delivery methods, EP has emerged as one of the most likely alternatives to AAV 17–21 because of its high transfection efficiency 22,23 and nontoxicity. 24…”
Section: Introductionmentioning
confidence: 99%
“…The MYCN A amplified RB1 -proficient retinoblastoma tumours also have distinct molecular signatures from RB1 -deficient tumours [ 5 ]. Tumorigenic growth can be induced with high frequency when MYCN is over-expressed in RB1 -proficient human retinal organoids as well as in embryonic chicken retina in vivo [ 7 ]. In both systems, the tumorigenic cells are anaplastic and express markers for active proliferation and undifferentiated cone photoreceptors (cPR) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%